Avocado rhizosphere community profiling: white root rot and its impact on microbial composition - Magagula, Phinda; Swart, Velushka; Fourie, Arista; Vermeulen, Alicia; Nelson, Johannes Harold; van Rooyen, Zelda; van den Berg, Noëlani (Frontiers in Microbiology, 2025)
IntroductionThe avocado rhizosphere supports diverse microbial communities essential for plant health and defence against pathogens. This study aimed to investigate the impact of Dematophora necatrix, the causal agent of white root rot (WRR), on the microbial composition and soil physicochemical properties of infected and non-infected avocado trees in two South African orchards.MethodsITS and 16S metabarcoding was used to compare the composition and diversity of the rhizosphere microbiome. Soil physicochemical properties were also assessed, and culturable bacterial and fungal isolates from the rhizosphere were screened for antagonistic activity against D. necatrix.ResultsWe found that D. necatrix did not significantly alter overall microbial diversity but influenced relative abundance of specific taxa. In Orchard A, dominant bacterial genera included Sphingomonas, Rokubacteriales and Lysobacter, while Orchard B featured Sphingomonas and Acidothermus while beneficial microbes such as Streptomyces and Bacillus were enriched in WRR non-infected (WRR-N) soils. The fungal profiles revealed Trichoderma and Penicillium as potential biocontrol agents enriched in WRR-N soils. Furthermore, dual-culture assays demonstrated that Bacillus, Pseudomonas, Penicillium and Trichoderma isolates inhibited D. necatrix, highlighting their biocontrol potential. Key parameters, such as soil pH and iron (Fe), correlated strongly with microbial composition, suggesting they play an important role in pathogen resilience.DiscussionThese findings underscore the complexity of the avocado rhizosphere and its role in managing WRR, offering a foundation for developing integrated disease management strategies to enhance avocado productivity.